2012
DOI: 10.1128/mcb.00496-12
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Negatively Regulates the Activities, Functions, and Protein Levels of hMOF and TIP60

Abstract: b SIRT1 is a NAD؉ -dependent histone H4K16 deacetylase that controls several different normal physiologic and disease processes. Like most histone deacetylases, SIRT1 also deacetylates nonhistone proteins. Here, we show that two members of the MYST (MOZ, Ybf2/Sas3, Sas2, and TIP60) acetyltransferase family, hMOF and TIP60, are SIRT1 substrates. SIRT1 deacetylation of the enzymatic domains of hMOF and TIP60 inhibits their acetyltransferase activity and promotes ubiquitination-dependent degradation of these prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 91 publications
6
85
2
Order By: Relevance
“…Therefore, sirtuins may regulate multiple members of the NuA4 complex. In line with this observation, Peng et al previously described the SIRT1-regulated acetylation of the Esa1-like TIP60 and hMOF catalytic subunits in mammalian cells (39).…”
Section: Fig 4 Analysis Of Sites Targeted By Sirtuin Gcn5 and Esa1mentioning
confidence: 53%
“…Therefore, sirtuins may regulate multiple members of the NuA4 complex. In line with this observation, Peng et al previously described the SIRT1-regulated acetylation of the Esa1-like TIP60 and hMOF catalytic subunits in mammalian cells (39).…”
Section: Fig 4 Analysis Of Sites Targeted By Sirtuin Gcn5 and Esa1mentioning
confidence: 53%
“…SIRT1 reduced the TIP60 half-life (Fig. 3D) (20), whereas HDAC3 increased the TIP60 half-life (Fig. 3B), and this stabilization is dominant over the effects of SIRT1 because cotransfection of both HDAC3 and SIRT1 with TIP60 resulted in an increase in the TIP60 half-life (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The high efficiency of Sirt1 in deacetylating MYST proteins such as MOF and Tip60 was also confirmed by several other recent studies. 91,151 Enzymatic analysis with the MOF deac and Tip60 deac showed that, in the deacetylated state, the cognate substrate acetylation activity of both enzymes decreased only slightly (e.g., The HAT enzyme activity was commonly characterized by using the isotope-labeled Ac-CoA. Due to the high sensitivity, the radioactive assay is suitable for kinetic and functional study of HATs.…”
Section: Discussionmentioning
confidence: 99%
“…Seto and coworkers obtained deacetylated MOF by treatment with Sirt1/NAD + . 91 Interestingly, their studies showed that the deacetylation of MOF reduces the cellular protein stability of MOF. 91 It is known that the MYST HATs frequently exist as multi-protein complexes.…”
Section: Chapter 4 Conclusion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation